Anti-Dandruff Shampoo Formulation from Rambutan Leaf Extract (Nephelium lappaceum L.) as Antifungal Malassezia furfur - Azzahra, Hasna; Shalihah, Fianicha; Aeniah, Siti; Rahmawati, Inka Pungky; Ningrum, Paula Tyasmita Andar; Wardani, Salma Fauzia; Muslimah, Intan (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
A shampoo is a product that is used to maintain hair. The most common hair problem is dandruff. A microorganism that causes dandruff is Malassezia furfur. Malassezia furfur is the causative microorganism that infects the skin and scalp into dandruff. This fungus can grow quickly if the head has excess oil glands. Rambutan leaf extract contains secondary metabolites that can inhibit fungal growth. Alkaloids can inhibit the growth of fungi because fungi can grow well at a pH of 3,8 – 5,6. Flavonoids and tannins can cause damage to cell membrane proteins, causing changes in membrane permeability and fungal cell membrane lysis. Saponins can break down fungal cells. A shampoo formulation from Rambutan leaf extract sets it apart from other anti-dandruff shampoos because its herbal composition is safe and increases bioavailability benefits. The method used is laboratory experimental. This research procedure is making rambutan leaf extract using a rotary evaporator, making shampoo by compounding the formulation components, growing test mushrooms on PDA media, making test mushroom suspensions, and conducting the research and data collection. The result showed that shampoo from rambutan leaf extract has an inhibition zone diameter of 0.3 cm to 0.6 cm had a moderate growth inhibition response. The results of the antifungal activity test showed that the rambutan leaf extract shampoo concentration of 10%, 15% and 30% can inhibit the growth of fungi with the best inhibitory concentration at 30% in a strong category.